2023
DOI: 10.1101/2023.09.27.559686
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cytoplasmic fluidization triggers breaking spore dormancy in fission yeast

Keiichiro Sakai,
Yohei Kondo,
Yuhei Goto
et al.

Abstract: The cytoplasm is a complex, crowded environment that influences myriad cellular processes including protein folding and metabolic reactions. Recent studies have suggested that changes in the biophysical properties of the cytoplasm play a key role in cellular homeostasis and adaptation. However, it still remains unclear how cells control their cytoplasmic properties in response to environmental cues. Here, we used fission yeast spores as a model system of dormant cells to elucidate the mechanisms underlying reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…In contrast, a cAMP phosphodiesterase, Cgs2, negatively regulates the PKA activity by degrading cAMP (DeVoti et al, 1991;. The cAMP-PKA pathway plays a crucial role in divergent cellular processes in fission yeast such as stress resistance (Matsuo & Kawamukai, 2017), sexual differentiation (Maeda et al, 1994), spore germination (Hatanaka & Shimoda, 2001;Sakai et al, 2023), gluconeogenesis (Hoffman & Winston, 1991), cell size control (Kelkar & Martin, 2015;Uysal Özdemir et al, 2024), heterochromatin formation (Bao et al, 2022), and autophagy (Pérez-Díaz et al, 2023). Among these, it is well known that cAMP-PKA pathway represses the expression of Ste11, a key transcription factor for sexual differentiation, by inactivating the zinc finger transcription factor Rst2 (Otsubo & Yamamoto, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a cAMP phosphodiesterase, Cgs2, negatively regulates the PKA activity by degrading cAMP (DeVoti et al, 1991;. The cAMP-PKA pathway plays a crucial role in divergent cellular processes in fission yeast such as stress resistance (Matsuo & Kawamukai, 2017), sexual differentiation (Maeda et al, 1994), spore germination (Hatanaka & Shimoda, 2001;Sakai et al, 2023), gluconeogenesis (Hoffman & Winston, 1991), cell size control (Kelkar & Martin, 2015;Uysal Özdemir et al, 2024), heterochromatin formation (Bao et al, 2022), and autophagy (Pérez-Díaz et al, 2023). Among these, it is well known that cAMP-PKA pathway represses the expression of Ste11, a key transcription factor for sexual differentiation, by inactivating the zinc finger transcription factor Rst2 (Otsubo & Yamamoto, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a cAMP phosphodiesterase, Cgs2, negatively regulates the PKA activity by degrading cAMP (DeVoti et al, 1991; Mochizuki & Yamamoto, 1992). The cAMP-PKA pathway plays a crucial role in divergent cellular processes in fission yeast such as stress resistance (Matsuo & Kawamukai, 2017), sexual differentiation (Maeda et al, 1994), spore germination (Hatanaka & Shimoda, 2001; Sakai et al, 2023), gluconeogenesis (Hoffman & Winston, 1991), cell size control (Kelkar & Martin, 2015; Uysal Özdemir et al, 2024), heterochromatin formation (Bao et al, 2022), and autophagy (Pérez-Díaz et al, 2023). Among these, it is well known that cAMP-PKA pathway represses the expression of Ste11, a key transcription factor for sexual differentiation, by inactivating the zinc finger transcription factor Rst2 (Otsubo & Yamamoto, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The coupling between crowding level and cell physiology makes cell density a key proxy for characterizing fundamental cellular processes such as proliferation, apoptosis, metabolic shifts, and differentiation 1,3 , indicating its potential as a biomarker for cellular fitness and drug response. Studies on single-cell organisms such as bacteria and yeast have reported that molecular crowding levels significantly change during cell state transitions between proliferation and dormancy, and density is thought to acutely reflect these transitions 58 . Whether such connections between density and proliferation exist in primary mammalian cells remains unclear, in part due to limitations in existing density measurement methods.…”
mentioning
confidence: 99%